2018
DOI: 10.1007/978-3-319-96145-3_8
|View full text |Cite
|
Sign up to set email alerts
|

Model Checking Quantitative Hyperproperties

Abstract: Abstract. Hyperproperties are properties of sets of computation traces. In this paper, we study quantitative hyperproperties, which we define as hyperproperties that express a bound on the number of traces that may appear in a certain relation. For example, quantitative non-interference limits the amount of information about certain secret inputs that is leaked through the observable outputs of a system. Quantitative noninterference thus bounds the number of traces that have the same observable input but diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 41 publications
0
44
0
Order By: Relevance
“…HyperLTL [8] is a successor of the temporal logic SecLTL [14] used to characterize temporal information flow. The model-checking [8,25,26], satisfiability [18,19,21], monitoring problem [1][2][3][4][22][23][24]33,34], and the first-order extension [31] of HyperLTL have been studied before. In [11], it has been shown that existential quantification in a HyperLTL formula can be reduced to strategic choice.…”
Section: Related Workmentioning
confidence: 99%
“…HyperLTL [8] is a successor of the temporal logic SecLTL [14] used to characterize temporal information flow. The model-checking [8,25,26], satisfiability [18,19,21], monitoring problem [1][2][3][4][22][23][24]33,34], and the first-order extension [31] of HyperLTL have been studied before. In [11], it has been shown that existential quantification in a HyperLTL formula can be reduced to strategic choice.…”
Section: Related Workmentioning
confidence: 99%
“…Related Work. While the verification of general HyperLTL formulas has been studied before [6,17,18], there has been, so far, no practical model checking algorithm for HyperLTL formulas with quantifier alternation. The existing algorithm involves a complementation of the system automaton, which results in an exponential blow-up of the state space [18].…”
Section: Introductionmentioning
confidence: 99%
“…HyperLTL has been used extensively to specify hyperproperties of practical interest (e.g. [14,21,[23][24][25][26]). For example, observational determinism is expressed as the following formula:…”
Section: Introductionmentioning
confidence: 99%
“…Efficient model checking, synthesis, and satisfiability checking tools for HyperLTL already exist [12,[19][20][21][22]25,26]. Implementing an efficient runtime verification tool for HyperLTL specifications is, despite recent theoretical progress [1,[5][6][7]24,28,29,37], difficult: In principle, the monitor not only needs to process every observed trace, but must also store every trace observed so far, so that future traces can be compared with the traces seen so far.…”
Section: Introductionmentioning
confidence: 99%